PIERWSZY BANK STANÓW ZJEDNOCZONYCH JAKO PIERWOWZÓR SYSTEMU REZERWY FEDERALNEJ - Kwiatkowski, Wojciech (Zeszyty Prawnicze, 2017)
First Bank of the United States as a Prototype for the Federal Reserve System Summary The article describes the history of the First Bank of the United Statesfirst banking- institution, that was charted in XVII-th century North America as an effect of a cooperation of two federal bodies – Congress and the President. Although, the federal government possessed only 20 %, of the shares with federal licences it could conduct its activity on territory of the whole country. Moreover – the Bank is now referred to as the first central bank in the United States because of its national scope and services rendered to the federal government. The Bank helped the government to obtain emergency loans, facilitated the payment of taxes, and served as the receiver and disburser of the public funds. In addition, it issued bank notes and made them fully redeemable in coin. During a 20-years period the Bank achieved a commercial success and maintained a financial stability. However, in 1811 Congress did not renew the charter because the Bank’s constitutionality was questioned. Alexander Hamilton (the first U.S. Secretary of the Treasury), who was [the followerof creation of the bank, already in 1790 assumed that the federal government had the power to charter banks because the Constitution granted the government the right to establish institutions necessary for its operations. Addifferent viewpoint was presented by Thomas Jefferson who favored a more decentralized government and believed that only the states could charter banks under the Constitution. Furthermore – because the Constitution did not expressly grant the power to Congress, he reasoned that federally chartered banks were unconstitutional. Finally in 1819, as a far-reaching decision, the Supreme Court Chief Justice John Marshall followed Hamilton’s reasoning and ruled in case McCulloch vs Maryland that the Second Bank of the United States was constitutional. For U.S. federal government this decision of the Supreme Court was very important about 200 years later – in 1913, when president Wilson, many politicians’ and main U.S. bankers decided to create the Federal Reserve System.